2019
DOI: 10.1111/ele.13222
|View full text |Cite
|
Sign up to set email alerts
|

The shape of abundance distributions across temperature gradients in reef fishes

Abstract: Improving predictions of ecological responses to climate change requires understanding how local abundance relates to temperature gradients, yet many factors influence local abundance in wild populations. We evaluated the shape of thermal‐abundance distributions using 98 422 abundance estimates of 702 reef fish species worldwide. We found that curved ceilings in local abundance related to sea temperatures for most species, where local abundance declined from realised thermal ‘optima’ towards warmer and cooler … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
79
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(84 citation statements)
references
References 50 publications
(100 reference statements)
4
79
1
Order By: Relevance
“…As an omnivorous bentho-pelagic feeder, Dascyllus aruanus can consume zooplankton and algae in equal proportions [34,38] which may partially explain its high abundance in slope/base habitats. Environmental factors such as water temperature, salinity, predators, conspecifics, and prey availability are also likely to influence the distribution and abundance of damselfish, independent of the abundance or availability of suitable coral hosts [34,37,83]. Although structural complexity and subsequent coral cover are often positively associated with fish biodiversity [1,4], results of this study showed that these two variables did not predict occupancy or biomass of coral-dwelling damselfish that closely associate with corals, consistent with previous studies [7,9,25,[84][85][86].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…As an omnivorous bentho-pelagic feeder, Dascyllus aruanus can consume zooplankton and algae in equal proportions [34,38] which may partially explain its high abundance in slope/base habitats. Environmental factors such as water temperature, salinity, predators, conspecifics, and prey availability are also likely to influence the distribution and abundance of damselfish, independent of the abundance or availability of suitable coral hosts [34,37,83]. Although structural complexity and subsequent coral cover are often positively associated with fish biodiversity [1,4], results of this study showed that these two variables did not predict occupancy or biomass of coral-dwelling damselfish that closely associate with corals, consistent with previous studies [7,9,25,[84][85][86].…”
Section: Discussionsupporting
confidence: 84%
“…Clearly, studies of coral-associated fauna across multiple spatial scales [30] that go beyond simply quantifying fauna presence-absence are necessary to understand the population dynamics of corals and symbiotic fauna. Quantifying the establishment and maintenance of such symbiotic associations with scleractinian corals will be essential to predicting how these complex networks operate under global environmental stress [83]. Indeed, many of these branching coral species, particularly, Seriatopora hystrix, which hosts the highest damselfish biomass, are the species most vulnerable to global climate change [51,106]; the loss of these coral species will reduce considerably the habitat for small-bodied fishes [22].…”
Section: Discussionmentioning
confidence: 99%
“…According to the abundant-centre hypothesis, species should have higher population density in the centre of their geographic distribution (Brown 1984, Sagarin andGaines 2002). However, empirical support for this remains fairly low (Pironon et al 2016, Dallas et al 2017) (but see Waldock et al 2019), as this hypothesis makes numerous assumptions concerning the geographic distribution of a species. For instance, populations are assumed to be well connected throughout the geographic range, be at are largely untenable (Sagarin et al 2006, Dallas et al 2017, Santini et al 2019.…”
Section: Introductionmentioning
confidence: 99%
“…It is potentially due to these factors that the abundantcentre and abundant-niche centre hypotheses have received mixed support so far in natural systems. Understanding when and why we observe abundant-centre and abundantniche centre relationships (Martínez-Meyer et al 2013, Waldock et al 2019, Osorio-Olvera et al 2020, and when we do not (Sagarin and Gaines 2002, Pironon et al 2016, Dallas et al 2017, Santini et al 2019) is a pressing need. Presently, abundant-centre relationships are largely a collection of observational studies at different scales and encompassing a wide range of taxa, but without any clear consensus or synthetic understanding of the underlying cause (Sagarin andGaines 2002, Pironon et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The growth rate curve for different taxa may be not always unimodal, that is species growth rate may not be optimal in the centre of the environmental niche (Dallas, Decker, & Hastings, 2017), and show leftward‐ or rightward‐skewed shapes over a particular environmental gradient (Figure 1b,c; Waldock, Stuart‐Smith, Edgar, Bird, & Bates, 2019). In a left‐skew case, α‐diversity could possibly be underestimated at a certain environmental gradient of site s1 because it was expected to be observed but was not in the model.…”
Section: Discussionmentioning
confidence: 99%